The Nature and Nurture of Congenital Amusia: A Twin Case Study - Pfeifer, Jasmin; Hamann, Silke (Frontiers in Behavioral Neuroscience, 2018)
In this paper we report the first documented case of congenital amusia in dizygotic twins. The female twin pair was 27 years old at the time of testing, with normal hearing and above average intelligence. Both had formal music lesson from the age of 8 to 12 and were exposed to music in their childhood. Using the Montreal Battery of Evaluation of Amusia (Peretz et al. 2003), one twin was diagnosed as amusic, with a pitch perception as well as a rhythm perception deficit, while the other twin had normal pitch and rhythm perception. We conducted a large battery of tests assessing the performance of the twins in music, pitch perception and memory, language perception and spatial processing. Both showed an identical albeit low pitch memory span of 3.5 tones and an impaired performance on a beat alignment task, yet the non-amusic twin outperformed the amusic twin in three other musical and all language related tasks. The twins also differed significantly in their performance on one of two spatial tasks (visualization), with the non-amusic twin outperforming the amusic twin (83% vs. 20% correct). The performance of the twins is also compared to normative samples of normal and amusic participants from other studies. This twin case study highlights that congenital amusia is not due to insufficient exposure to music in childhood: The exposure to music of the twin pair was as comparable as it can be for two individuals. This study also indicates that there is an association between amusia and a spatial processing deficit (see Douglas & Bilkey 2007; contra Tillmann et al. 2010; Williamson et al. 2011) and that more research is needed in this area.